Influence of Time of Weed Removal on Maize Yield and Yield Components Based on Different Planting Patterns, the Application of Pre-Emergence Herbicides and Weather Conditions - Dejan Nedeljković; Dragana Božić; Goran Malidža; Miloš Rajković; Stevan Z. Knežević; Sava Vrbničanin (Plants)
The crop yield can be affected by many factors, including various levels of weed presence. Therefore, we conducted a study to evaluate the effect of time of weed removal in combination with planting pattern and pre-emergence-applied herbicides on maize yield and yield components in 2015, 2016 and 2017. The experiments were designed in a split–split plot arrangements with three replications, which consisted of the two main plots (standard/conventional and twin-row planting pattern), two subplots (with and without pre-emergence herbicide application) and seven sub-subplots (seven weed removal timings). In the dry season of 2015, maize yield was much lower (413–9045 kg ha−1) than in the wet 2016 seasons with yields of 5759–14,067 kg ha−1 across both planting patterns. Yield and yield components were inversely correlated with the time of weed removal. The application of pre-emergence herbicides delayed the critical time for weed removal (CTWR), which ranged from V4 to V10 and from V3 to V11 for standard and twin-row planting patterns, respectively. Herbicides also protected various yield components, including 1000 seeds weight and number of seeds per cob.